STUDI PENDAHULUAN ALTERASI DAN MINERALISASI DI DUSUN DAGEN, DESA GEMAHARJO, KECAMATAN TEGALOMBO, KABUPATEN PACITAN, PROVINSI JAWA TIMUR - Danis Agoes Wiloso; R.Aditya Manggala Yudha (PROSIDING SNAST, 2018)
Dagen and vicinity have the potential of metal resources and epithermal mineralization systems characterized by the presence of alteration and quartz sulphide veins. The veins are formed as a result of the filling process on the fracture by a hydrothermal solution. Identification of vein characteristics needs to be studied in metal exploration to assist in the development of economical mineral exploration activities. The purpose of this study was to investigate the characteristics of quartz veins and to determine the vein distribution and zoning deposition of mineralization in the study area.The research was conducted in May 2018 located in Dagen Village, Gemaharjo Village, Tegalombo District, Pacitan Regency, East Java Province precisely located at coordinates between 536055 - 538104 mN and 9110712 - 9108008 mE with the research area is 3.58 km2. Sampling for analysis mineragrafi as much as 3 sample of quartz vein with selective sampling.The results showed vein texture in research area in the form of massive, banded, crustiform, comb, and cockade. The dominant vein texture contains a base metal and into the Crystalline Quartz (X) Super Zone. Mineragraphy analysis results from 3 quartz vein samples showed mineral content of chalcopyrite, sphalerite, tennantite, galena, covellite, native element Au and Ag. It proves that the research area is a place of accumulation of base metal minerals and little precious metals from the epithermal mineralization system.